Meteoric smoke and H2SO4 aerosols in the upper stratosphere and mesosphere. Issue 2 (27th January 2017) - Hervig, Mark E.; Bardeen, Charles G.; Siskind, David E.; Mills, Michael J.; Stockwell, Robert
Abstract: Meteoric smoke has traditionally been understood as a passive tracer which follows the global mesospheric circulation. Smoke extinction measured by the Solar Occultation For Ice Experiment, however, shows that while this is true in the middle to upper mesosphere (pressure <~0.2 hPa), it is not true near the stratopause. Here the expected winter increase begins 3 months earlier than in models. We suggest that the autumn extinction increase is due to H2 SO4 condensing above the nominal stratospheric aerosol layer (~5 hPa). This is possible due to lowering of the H2 SO4 saturation vapor pressure when the acid is neutralized through combination with meteoric metals. The appearance of neutralized H2 SO4 aerosol in autumn is associated with the seasonal decrease in temperature. The combination of meteoric smoke and neutralized H2 SO4 aerosols explains the observations and supports previous suggestions that H2 SO4 could condense above the nominal stratospheric sulfate layer. Key Points: Observed meteoric smoke extinction behaves as a tracer in the midmesosphere but not near the stratopause H2 SO4 saturation vapor pressures can be reduced through neutralization with meteoric metals Annual cycle of aerosol extinction near the stratopause is explained by meteoric smoke and an autumnal layer of neutralized H2 SO4 aerosols